(Rheology its principel and aplication in food industry) - Yulistia, Aan (Balai Besar Industri Agro, 1995)
Rheology has been defined as a science of deformation and flow of mater.Rheology has been applied in food for various purposes and its applications become wider with the progress of instrumentation and microcomputer.The fundamental method which has several advantages compared to imitatif and empiric methods,is used to provide more basic information of rheological properties of food.The understanding of fundamental method,therefore, is requried in order to use this method for food development.Â Â Â